Observation of ground state of ⁴H in ³H(α,τt)n reaction - Gorpinich, O.K.; Povoroznyk, O.M.; Jachmenjov, O.O. (Вопросы атомной науки и техники, 2004)
In kinematical complete investigation of ³H(α,τt)n reaction by using beam with Eα = 67.2 МеV and titan trituated target the ground state of ⁴Н was observed with Eg.s. = Ent = 3.22 ± 0.25 МеV and Г = 2.9 ± 1,1 МеV. В кінематично повному дослідженні ³H(α,τt)n-реакції з використанням пучка альфа-частинок з енергією
Еα = 67.2 МеВ і титан-тритієвої мішені спостерігався основний стан ядра ⁴Н з енергетичними параметрами
Еeо.с. = Еnt = 3.22 ± 0.25 МеВ та Г = 2.9 ± 1.1 МеВ. В кинематически полном исследовании ³H(α,τt)n-реакции с использованием пучка альфа-частиц с
энергией Eα = 67.2 МэВ и титан-тритиевой мишени наблюдалось основное состояние ядра ⁴Н с
энергетическими параметрами: Eо.с. = Ent = 3.22 ± 0.25 МэВ и Г = 2.9 ± 1.1 МэВ.